2022
DOI: 10.3389/fonc.2022.967342
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a prognostic signature for serous ovarian cancer based on lactate metabolism-related genes

Abstract: Background:The key biochemical feature of malignant tumor is the conversion of energy metabolism from oxidative phosphorylation to glycolysis, which provides sufficient capacity and raw materials for tumor cell rapid growth. Our study aims to construct a prognostic signature for ovarian cancer based on lactate metabolism-related genes (LMRGs).Methods: Data of ovarian cancer and non-diseased ovarian data were downloaded from TCGA and the GTEx database, respectively. LMRGs were obtained from GeneCards and MSigDB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…For example, a study reporting extraction of metabolism‐related genes from TCGA database identified a prognostic signature comprised of PTGIS, AOC3 and IDO1 28 . Meng et al 29 . screened TCGA and GTEx databases for differentially expressed genes in high‐grade serous ovarian cancer and demonstrated that these genes are involved in multiple metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study reporting extraction of metabolism‐related genes from TCGA database identified a prognostic signature comprised of PTGIS, AOC3 and IDO1 28 . Meng et al 29 . screened TCGA and GTEx databases for differentially expressed genes in high‐grade serous ovarian cancer and demonstrated that these genes are involved in multiple metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several systematic strati cation strategies have been developed to investigate OV metabolic heterogeneity [17,51,15,52,53,14]; however, they rarely consider MIPros. In this study, we not only rede ned and validated the OV subtypes based on the MPIscore in the TCGA-OV and GEO validation sets but also characterized the subtype-speci c clinical features, metabolism, genomic mutations, immune in ltration and regulations between the MPIscore groups, providing a comprehensive understanding of OV metabolism and guidelines for the precision diagnosis and treatment of OV.…”
Section: Discussionmentioning
confidence: 99%
“…(“Chen signature”), a prognostic model for platinum‐treated OC reported by Sabatier et al 25 . (“Sabatier signature”), a lactate metabolism‐related signature reported by Xiang et al 26 . (“Xiang signature”), a hematogenous and lymphatic metastasis signature reported by Yue et al 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The proportional hazards (PH) assumption was verified with the Schoenfeld test. Additionally, the 3-and 5-year ROC values of the GMPI were compared with those of other published gene signatures for OC, including a prognosisrelated genes signature reported by Chen et al 24 ("Chen signature"), a prognostic model for platinum-treated OC reported by Sabatier et al 25 ("Sabatier signature"), a lactate metabolism-related signature reported by Xiang et al 26 ("Xiang signature"), a hematogenous and lymphatic metastasis signature reported by Yue et al 27 ("Yue signature"), and an omentum metastasis-related prognostic signature reported by Zhang et al 28 ("Zhang signature"). Finally, the precision and accuracy of nomogram was evaluated with ROC curves, the Concordance index (C index) and restricted mean survival (RMS) time curves.…”
Section: Construction and Validation Of A Predictive Nomogrammentioning
confidence: 99%